2015
DOI: 10.1016/j.minpro.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu2+ activation on interfacial water structure at the sphalerite surface as studied by molecular dynamics simulation

Abstract: Keywords:MDS DFT Contact angle Interfacial water structure In the first part of this paper, an experimental contact angle study of fresh and Cu 2+ activated sphalerite-ZnS surfaces as well as the covellite-CuS (001) surface is reported describing the increased hydrophobic character of the surface during Cu 2+ activation. In addition to these experimental results, fresh sphalerite-ZnS (110), copper-zinc sulfide-CuZnS 2 (110), villamaninite-CuS 2 (100), and covellite-CuS (001) surfaces were examined using Molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…MD simulations based on the Universal force field parameters and Mulliken partial charges were conducted to assess the hydrophilicity of Cu 2+ activated sphalerite surface . The wettability of the pristine and the Cu 2+ -activated sphalerite was compared by calculating the contact angle, water number density distribution, water dipole orientation, and water residence time, among other things.…”
Section: Applications Of Molecular Modeling To Froth Flotationmentioning
confidence: 72%
See 1 more Smart Citation
“…MD simulations based on the Universal force field parameters and Mulliken partial charges were conducted to assess the hydrophilicity of Cu 2+ activated sphalerite surface . The wettability of the pristine and the Cu 2+ -activated sphalerite was compared by calculating the contact angle, water number density distribution, water dipole orientation, and water residence time, among other things.…”
Section: Applications Of Molecular Modeling To Froth Flotationmentioning
confidence: 72%
“…351 MD simulations based on the Universal force field parameters and Mulliken partial charges were conducted to assess the hydrophilicity of Cu 2+ activated sphalerite surface. 352 The wettability of the pristine and the Cu 2+ -activated sphalerite was compared by calculating the contact angle, water number density distribution, water dipole orientation, and water residence time, among other things. Although using a generic force field combined with Mulliken partial charges should be treated cautiously, the MD results confirmed that activating the sphalerite surface with Cu 2+ increases the mineral hydrophobicity due to decreased surface polarity.…”
Section: Mineral Surface Modification and Activation In Flotationmentioning
confidence: 99%
“…At higher concentration of copper precursor, the formation of protruding nanosheets of CuS in the aqueous phase and self-assembled spheres in the organic phase could be due to the partial wettability of CuS with water (contact angle of water with (001) plane of covellite CuS is 65°) and adsorption of electrolyte (Na 2 S). [39] CuS crystal structure is polar in the c-direction. During the initial stage of vertically growing CuS nanosheets, CuS clusters initially form, which can be wetted by water and adsorption of electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…Given the above, the presence of the Cu 2+ and Pb 2+ ions in process water within the differential flotation of Cu-Pb-Zn becomes relevant, and the fact of monitoring its variation to avoid inadvertently activating the Sphalerite is of utmost importance. The activation of Sphalerite by Cu 2+ ions has been previously studied (Gerson et al, 1999;Rao et al, 2011;Jin et al, 2015;Chen and Yoon, 2000) and it has been shown that Cu 2+ ions activate Sphalerite according to the following mechanism:…”
Section: Fig 4 Consumption Of Nacn In the Processmentioning
confidence: 99%
“…During the flotation of Pb-Cu-Zn sulfides ores, there are Cu 2+ , Pb 2+ , and Zn 2+ ions present. The Cu 2+ and Pb 2+ ions frequently cause inadvertent Sphalerite activation, promoting a reduction in the Cu concentrate grade (Rashchi et al, 2002;Jin et al, 2015;Aikawa et al, 2020). For example, this phenomenon occurs at Cozamin mine, located in Zacatecas, México, where after the grinding process, the pulp is fed into the flotation process: It begins with bulk copper-lead concentrate flotation with depressed zinc, and continues with the copper-lead separation and later with a subsequent flotation in a zinc circuit.…”
Section: Introductionmentioning
confidence: 99%